Early Diagnosis COVID-19 by Computed Tomography Scan - Abbood, Abbood Abbas (Journal of medical and pharmaceutical sciences, 2021)
COVID-19 is a virus that infects the respiratory system and causes pneumonia, kidney failure, and other health issues. The purpose of early diagnosis of COVID-19 is the fastest time to keep healthy cells for patients. A check-up for COVID-19 has been performed for patients whose ages were between (85–25) years by CT scan and laboratory-analysis (PCR) and X-ray and PET/CT scan. CT scan is considered the more clear method for the early diagnosis for COVID-19 because of the production of clear radiographic image quality and high-resolution and three-dimensional of a patient’s chest in two views (anterior-posterior view and the lateral view). In addition to that, a CT scan is more readily and cheaper, and more available in the hospital, also it takes less time to check the patient’s chest.